(untitled) (Al-Qamar, 2021)
The meaning which the word “Madrassa” bring forth in the Arabic language is the same which is given to word “School” in English language. Nevertheless, in olden days the word “Madrassa” was brought into use for the higher educational institutions in which the subject of Islamic law was taught routinely and occasionally other subjects, contrary to elementary schools which were usually recognized as “Kuttab or Maktab”. The usual word which is employed for the modern Arabic word, however is “Jamia”. Now a days, the Madrassa is such type of school in which Islamic law and theology is taught, usually affiliated with a Mosque and sponsored by the charitable trust which is widely known as “Wafaq”. Such as religious institutions brought revolutionary changes in the religious, economic and social set up of the Muslims of the Sub-Continent. Islamic culture, education and learning were promoted in the Sub-Continent with the efforts of religious scholars. When Muslims of Sub-Continent faced decline, these religious institutions also received great loss. But Muslim thinkers and Ullama motivated the “Deeni Madaris” without losing courage. Therefore, these Madaris proved extremely effective in the field of teaching and learning, the reason behind the effectiveness was the motivation of the Ullama who were playing important role. The prominent personalities like Maulana Muhammad Abid, Maulana Muhammad Qasim Nanotvi and Maulana Rasheed Ahmad Gangohi established Dar ul Uloom Deband in 1867, concentrating the religious and moral values of the Muslims. The objective of this article is to investigate the status, socio impact, and multi-dimensional role of the religious educational institution “ Jamia Dar ul Uloom Karachi” in Pakistan. Jamia Dar ul Uloom Karachi was founded by Mufti Muhammad Shafi on Shewal 11, 1370 AH. (June 1951) at Nanak Wara and later on it transferred to Korangi, Karachi, on Shaaban 15, 1376 AH. (March 17, 1957). This article will further explain how Jamia Dar ul Uloom Karachi was established in Karachi aimed prevalent Sufi shrines hegemony and practices and continued to grow in the environment. In a society, such as postcolonial Pakistan, faced with dramatic educational and strategic institutional transformation after the partition. Jamia Dar ul Uloom Karachi was able to show case itself as a different religious institution as well as imparting education in other subject too.